SECHA: A Smart Energy-Efficient and Cost-Effective Home Automation System for Developing Countries - Abdulhafiz Ahmed Mustofa; Yohannes Alemayehu Dagnew; Prabhakar Gantela; M. Javed Idrisi (Journal of Computer Networks and Communications)
Home automation systems are gaining a lot of attraction globally and changing the way we live. They simplify our lives, reduce workloads, improve home safety and security, and pave the way for newer developments. It is no wonder why these systems are in such high demand and why modernization is needed to keep up with consumer needs. Nevertheless, utilizing home automation system technology can be energy-intensive and costly—especially for middle-class families in developing countries. In this article, we discuss SECHA, a smart, energy-efficient, and cost-effective home automation system. It empowers users to automate their homes with IoT regardless of the residence type. SECHA is developed with the goal of being energy-efficient, simple to use, and open-source for everyone’s benefit. SECHA has developed a low-cost smart home automation system that incorporates Wi-Fi and GSM technology, enabling remote monitoring and control of appliances through an Android application. This solution enables users to easily monitor and manage their homes. An automation system has been developed using an ESP32 microcontroller equipped with Wi-Fi and GSM SIM800. This impressive setup is further enhanced by the integration of several sensors that enable monitoring of temperature, humidity, movement, and other aspects at home.